Daratumumab in severe Evans syndrome: a case report - Hillmann, Stefan M.; Brockhoff, Hendrik; Loebel, Sarah; Hentschke, Suna; Arnold, Dirk; Salwender, Hans (Frontiers in Hematology, 2026)
Evans syndrome is a rare autoimmune disorder characterized by the simultaneous or sequential occurrence of autoimmune cytopenia. The disease is chronic, relapsing, and frequently refractory to standard therapies. Typical symptoms include anemia-related fatigue, pallor, and jaundice due to hemolysis and petechiae, and purpura and mucosal bleeding due to thrombocytopenia. Treatment often involves a stepwise escalation of immunosuppressive treatments (e.g., corticosteroids, anti-CD20 monoclonal antibodies) and/or stimulants (e.g., thrombopoietin receptor agonists). However, sustained remission remains elusive in many patients. We report the case of a 69-year-old woman with a 19-year history of Evans syndrome, presenting with a life-threatening relapse marked by severe thrombocytopenia and strong hemolytic activity. The patient had previously undergone multiple treatment regimens and had developed comorbidities that both complicated disease management and treatment strategies. Despite repeated therapeutic interventions with various immunosuppressant agents, she remained transfusion-dependent and clinically unstable and experienced various treatment complications. Additionally, targeting antibody-producing plasma cells with daratumumab (anti-CD38) led to a rapid fall in transfusion dependency, clinical stabilization, and transition to outpatient care. Unfortunately, the patient later succumbed to infectious complications after a femoral fracture. This case underscores the therapeutic complexity of multirefractory Evans syndrome and the limitations of conventional therapy. The addition of daratumumab, resulting in depletion of CD38+ plasma cells, helped achieve hematologic stabilization in this refractory case.